PENGARUH KONSENTRASI GULA, WAKTU PENGERINGAN DAN SUHU PENGERINGAN TERHADAP KADAR GULA REDUKSI, TOTAL FENOL, DAN VITAMIN C, SERTA KARAKTERISTIK RASA MANISAN SALAK PONDOH KERING - Prastianti, Litarasmi; Budianta, Dwi Wibawa; Utomo, Adrianus Rulianto (Widya Mandala Surabaya Catholic University, 2016)
Salak is one of climacteric fruit native to Indonesia and became a mainstay of horticultural commodities that are exported to foreign countries, such as China, Malaysia, and Singapore. Salak has a high production quantities, it is because salak can bear fruit throughout the year. Salak is rich in a number of functional nutritional components such as phenols and vitamin C, but it is easily damaged after harvest. One attempt to extend its shelf life is by processing salak into dried candied salak. In this study, candied dried salak pondoh made with various concentrations of sugar concentration, drying time and drying temperature. The use of these treatments aim to determine precise variation which is results dried candied salak with the best functional component content. This study uses data analysis in the form of a response surface model consists of three (3) factors which sugar concentration (40%; 60%; 80%), drying time (4 hours, 5 hours, 6 hours), and drying temperature (70°C, 80°C, 90°C), with three repetitions of samples. Parameters to be tested are reducing sugar, total phenolic, vitamin C content, and taste. Results of organoleptic taste test were analyzed using ANOVA, while optimization of reducing sugar, total phenolic, vitamin C content, analyzed with RSM (Response Surface Method) and Box-Behnken design using Minitab software 16. Variations in research led to an increase of reducing sugars and total phenol content but decrease of vitamin C content. Variation of the research did not leave a noticeable difference at α = 5% for the taste characteristic of candied dried salak pondoh. Based on the results obtained by the formula optimization, sugar concentration of 80%, drying time of 6 hours, a drying temperature of 70°C produce candied dried salak pondoh with the lowest reduction sugar content, and the highest total phenolic and vitamin C content.